2005
DOI: 10.1007/s10567-005-8808-z
|View full text |Cite
|
Sign up to set email alerts
|

Pure Versus Co-occurring Externalizing and Internalizing Symptoms in Children: The Potential Role of Socio-Developmental Milestones

Abstract: Co-occurring internalizing and externalizing disorders are moderately prevalent in children, adolescents, and adults (Anderson, Williams, McGee, & Silva, 1987; McConaughy & Skiba, 1994), but much remains to be understood regarding why some children show "pure" versus co-occurring internalizing and externalizing symptoms. One possible influence that has previously not been considered is the failure to attain socio-developmental milestones, which paradoxically may prevent the development of co-occurring symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
123
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 194 publications
(201 reference statements)
20
123
0
5
Order By: Relevance
“…The comorbidity displayed for adoptees is close to the moderate to high coefficients usually reported in previous research conducted with adolescents in clinical and non-clinical samples (McConaughy & Achenbach, 1994;McConaughy & Skiba, 1994;Oland & Shaw, 2005;Zahn-Waxler, Klimes, & Slattery, 2000). On the contrary, the EB-IB comorbidity of r(32) = .19 found among controls is very unusual.…”
Section: Discussionsupporting
confidence: 85%
“…The comorbidity displayed for adoptees is close to the moderate to high coefficients usually reported in previous research conducted with adolescents in clinical and non-clinical samples (McConaughy & Achenbach, 1994;McConaughy & Skiba, 1994;Oland & Shaw, 2005;Zahn-Waxler, Klimes, & Slattery, 2000). On the contrary, the EB-IB comorbidity of r(32) = .19 found among controls is very unusual.…”
Section: Discussionsupporting
confidence: 85%
“…As shown by numerous studies (LaGreka & Lopez, 1998;Mahon et al, 2006;Oland &Shaw, 2005) is not surprising that our research showed that the largest number of students with internalized behavior problems (53.36%) belongs to the category of risk level of social competence and risky levels of antisocial behavior. These levels are more frequent in girls and with increasing age and declining record the scores on the scale, which means that with increasing age of the students have all the lower level of social functioning.…”
Section: Social Functioning Of Students With Internalizing Behavioralsupporting
confidence: 72%
“…Persons who have internalizing problems show considerable inhibition, difficulty to start communication and reluctance to approach others, even if they want to (Kingery et al, 2010). Most often they avoid situations in which one can see their lack of social competence and self-efficacy (Alfano, Beidel & Turner, 2006;Smari, Pétursdóttir & Porsteinsdóttir, 2001), making it difficult to acquire a positive self-image (Oland & Shaw, 2005). They are extremely careful with social norms and show excessive self-control (Hannesdottir & Ollendick, 2007), they are unsure when they run into obstacles, withdrawn, easily confused, and show a lack of self-confidence (Greco & Morris, 2005).…”
Section: Social Functioning Of Students With Internalizing Behavioralmentioning
confidence: 99%
“…We note that externalizing and internalizing symptoms have been related to cortisol levels in young children, although results of previous studies have not been consistent (e.g., Alink et al, 2008;Eisenberg et al, 2010;Gunnar et al, 2009;Ruttle et al, 2011). We also note that externalizing and internalizing disorders are frequently comorbid, although there is evidence that their trajectories and predisposing factors may differ, at least in some children (review in Oland & Shaw, 2005).…”
Section: Developmental Psychobiologymentioning
confidence: 58%